Interaction effect of phosphorus and sulphur fertilization on yield attributes, oil content, nutrient content and nutrient uptake of soybean [Glycine max (L.) Merrill] - Manoj, M.K. Sharma,; Harphool Meena,; Vinod Kumar Yadav,; Shankar Lal Yadav,; Rajendra K. Yadav, (Annals of Agricultural Research, 2024)
An experiment was conducted at Instructional Farm, College of Agriculture, Ummedganj, Kota, Rajasthan during kharif season of 2021. The treatments comprised four phosphorus levels viz., 0, 20, 40 and 60 kg ha-1 and three sulphur levels viz., 15, 30 and 45 kg ha-1, thereby making twelve treatment combinations under factorial randomized block design replicated three times. Maximum no. of pods (50 plant-1) and test weight (131.95 g) were noted at application of 60 kg P2O5 ha-1 along with 45 kg sulphur ha-1, which was significantly higher over application of 40, 20 kg P2O5 ha-1 and control along with 15, 30 and 45 kg sulphur ha-1, irrespectively and rest of the treatment combinations in soybean. However, it was found at par with application of 60 kg P2O5 ha-1 along with 30 kg sulphur ha-1. The maximum phosphorus content (0.675 %) in seed and total phosphorus uptake by soybean crop (20.73 kg ha-1) were noted at 60 kg P2O5 ha-1 along with 45 kg sulphur ha-1 over application of 40, 20 kg P2O5 ha-1 and control along with 15, 30 and 45 kg sulphur ha-1, irrespectively. Significantly higher sulphur content (0.497 %) in seed and total sulphur uptake by soybean crop (19.51kg ha- 1) was recorded with application of 60 kg P2O5 ha-1 along with 45 kg sulphur ha-1 over application of 40, 20 kg P2O5 ha-1 and control in combination with 15, 30 and 45 kg sulphur ha-1, during the investigation. Significantly higher oil content (20.95 %) was noted at 60 kg P2O5 ha-1 along with 45 kg sulphur ha-1 which was found at par with application of 60 kg P2O5 ha-1 along with 30 kg sulphur ha-1(20.72 %) over application of 40, 20 kg P2O5 ha-1 and control along with application of 15, 30 and 45 kg sulphur ha-1 and rest of the treatment combinations.